Collocated social practices surrounding photos - Lindley, Siân; Durrant, Abigail; Kirk, David; Taylor, Alex (CHI 2008 Extended Abstracts, 2008)
Recent developments in technology mean that it is becoming increasingly possible to support collaboration around digital photos. This makes an exploration of the existing collocated social practices that are associated with photos both timely and relevant. This workshop will explore social practices in the areas of photowork, photo sharing and photo displays, with the aim of drawing together current research and considering how the findings might inform technology innovation.